Are We Facing a Fundamental Challenge to Higher Education Internationalization? - Altbach, Philip; de Wit, Hans (International Higher Education, 2018)
The global landscape for higher education internationalization is changing dramatically. What one might call “the era of higher education internationalization” might either be finished or, at least, be on life support. In addition to nationalist-populist factors, issues of academic freedom, ethics, the role of English, shifting patterns in student mobility, and concerns about transnational education, are challenging the future of internationalization. The current criticism about the unlimited growth of teaching in English, recruitment of international students and development of branch campuses, is coming from two completely opposite sources. On the one hand, there is the nationalist–populist argument of anti-international and anti-immigration. More relevant is the concern about quality, academic freedom, and ethics in the higher education community itself.